Rcirc: An R Package for circRNA Analyses and Visualization - Sun, Peisen; Wang, Haoming; Li, Guanglin (Frontiers in Genetics, 2020)
Circular RNA (circRNA), which has a closed-loop structure, is a special type of endogenous RNA that plays important roles in many biological processes. With improvements in next-generation sequencing technology and bioinformatics methods, some tools have been published for circRNA detection based on RNA-seq. Here, we developed the R package ‘Rcirc’ for further analyses of circRNA after its detection. Rcirc identifies the coding ability of circRNA and visualizes various aspects of this feature. It also provides general visualization for both single circRNAs and meta-features of thousands of circRNAs. Rcirc was designed as a user-friendly tool that provides many highly automated functions without requiring the user to perform many complicated processes by users. It is available on GitHub (https://github.com/PSSUN/Rcirc) under the license GPL 3.0.